POLITICAL ALLEGORY IN THE LITERARY WORKS OF SHASHI THAROOR - Mali, Rakesh S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper explores the intricacies of political allegory in Shashi Tharoor’s novels, "The Great Indian Novel" and "Riot: A Love Story." Through reimagining historical events and characters, Tharoor uses political allegory to critique and reflect on socio-political issues of India. The study examines narrative structures, character representations, and thematic elements to uncover the layers of meaning in Tharoor’s allegorical narratives. It demonstrates how these narratives serve as a commentary on the political and social realities of India. By analyzing Tharoor’s use of political allegory, this research contributes to the broader discourse on the role of allegory in literature and highlights the relevance of Tharoor’s works in understanding Indian political history and culture, enriching the field of contemporary Indian literature.